Metrological Support for the Measurement of Tribological Properties of Carbon-carbon Composite in Braking Devices - Alisin, V. V. (Advanced Aspects of Engineering Research Vol. 11, 2021)
The article is focused on the accuracy of quantification for the tribological properties of a frictional carbon-carbon material during braking. Carbon-carbon materials are among the most promising materials for large use in friction units of braking devices for transport facilities. The experiments were performed with the IM-58 frictional testing machine when the rotating shaft with a previously established flyweight was in the braking mode. The tests for frictional heat resistance were performed with 2168 UMT. The research deals with the changes in friction and wear properties under the conditions of sample heating. The paper describes accuracy characteristics for the measured tribological properties. The maximum permissible temperature of frictional heating in terms of wear was established for reliable operation of the brake unit.